1994
DOI: 10.1159/000217913
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Polypeptide-Specif ic Antigen and CA 125 as Serum Tumor Markers in Ovarian Carcinoma

Abstract: The serum levels of tissue polypeptide-specific (TPS) antigen were measured using the M3 monoclonal antibody in an enzyme immunoassay in 33 patients with ovarian cancer, in 26 women with benign pelvic masses and in 26 women with a laparoscopically proven normal pelvis. The results were compared with the serum levels of the CA 125 antigen. At a cutoff level of 135 U/l for TPS and 20 U/l for CA 125 (95th percentile of the healthy controls), the sensitivity of the tests for detecting a malignant tumor was 77% for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Serum Tg measurements have little clini-cal utility for diagnosis of thyroid carcinoma. TPA was identified in various kinds of carcinomas and carcinoma cell lines by Björklund (17) using antibodies raised against insoluble residuces extracted from pooled human tumor, and has been recognized as a good tumor marker (3,(6)(7)(8)(9)(10)(11). TPA was identified in various kinds of carcinomas and carcinoma cell lines by Björklund (17) using antibodies raised against insoluble residuces extracted from pooled human tumor, and has been recognized as a good tumor marker (3,(6)(7)(8)(9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum Tg measurements have little clini-cal utility for diagnosis of thyroid carcinoma. TPA was identified in various kinds of carcinomas and carcinoma cell lines by Björklund (17) using antibodies raised against insoluble residuces extracted from pooled human tumor, and has been recognized as a good tumor marker (3,(6)(7)(8)(9)(10)(11). TPA was identified in various kinds of carcinomas and carcinoma cell lines by Björklund (17) using antibodies raised against insoluble residuces extracted from pooled human tumor, and has been recognized as a good tumor marker (3,(6)(7)(8)(9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Björklund et al (5) described that among 35 epitopes of TPA, the M3 epitope characterized proliferating tumor cells. Tissue polypeptide specific antigen (TPA) is a marker utilizing a specific epitope of TPA and is able to assist in predicting prognosis and response to treatment in a variety of cancers, including lung (6), breast (7), prostatic (8), pancreatic (9), ovarian (10), and cervical cancers (11). The TPS level in serum does not simply reflect the mass of the tumor, as is assumed for other tumor markers, but reflects the tumor cell activity (5).…”
Section: Introductionmentioning
confidence: 99%
“…The value of this tumor marker was investigated in clinical trials on breast [10,11], ovary [12], prostate, renal [9,13], and colon [14] cancer.…”
Section: Introductionmentioning
confidence: 99%
“…High levels of TPS and CA125 were also reported in ovarian cancer compared to benign gynecological diseases. TPS and CA125 were higher in advanced stages of cancer compared to early stages (2,16). It was observed that serum TPS and CA125 reflect the course of the neoplastic process during chemotherapy (17).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that serum TPS and CA125 reflect the course of the neoplastic process during chemotherapy (17). Also, TPS and CA125 levels could be used as good predictors of recurrence in ovarian cancer (16). TPS in combination with CA125 has improved the detection of recurrent ovarian cancer (8) and in combination they increase the prognostic accuracy after chemotherapy (18).…”
Section: Discussionmentioning
confidence: 99%